2023
DOI: 10.21037/jgo-23-71
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor location impacts survival in colorectal cancer patients after primary resection: a population‑based propensity score matching cohort study

et al.

Abstract: Background: Right-sided colon cancers (R-CCs) are associated with worse outcomes compared to leftsided colon cancers (L-CCs). This study aimed to investigate whether a difference in survival existed among R-CC, L-CC, and rectal cancer (ReC) and subsequent liver metastasis.Methods: Data from the Surveillance, Epidemiology, and End Results (SEER) database for 2010-2015 was used to identify colorectal cancer (CRC) patients who underwent surgical resection of primary disease.Propensity score adjustment and Cox reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…A few studies have shown that the primary tumor site (left vs. right colon) appears to influence long-term outcomes after resection of liver and lung metastases of CRC origin but reached conflicting results of which location has the worst survival [127][128][129]. Other studies did not identify any prognostic value of the primary tumor site on the long-term outcomes after resection for liver or lung metastases of CRC origin [121,130], as was the case in the present study for SM of CRC origin.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown that the primary tumor site (left vs. right colon) appears to influence long-term outcomes after resection of liver and lung metastases of CRC origin but reached conflicting results of which location has the worst survival [127][128][129]. Other studies did not identify any prognostic value of the primary tumor site on the long-term outcomes after resection for liver or lung metastases of CRC origin [121,130], as was the case in the present study for SM of CRC origin.…”
Section: Discussionmentioning
confidence: 99%